Experiences of Clinical Clerkship Students With Mindfulness-Based Stress Reduction: A Qualitative Study on Long-Term Effects - van Dijk, Inge; van Beek, Maria H. C. T.; Arts-de Jong, Marieke; Lucassen, Peter L. B. J.; van Weel, Chris; Speckens, Anne E. M. (Frontiers in Psychology, 2022)
Purpose To explore the mindfulness practice, its long-term effects, facilitators and barriers, in clinical clerkship students two years after participation in an eight-week mindfulness-based stress reduction (MBSR) training. Method A qualitative study was performed by semi-structured in-depth interviews with of 16clinical clerkship students selected by purposive sampling. Students had participated in a MBSR training two years before and were asked about their current mindfulness practice, and the long-term effects of the MBSR training. Thematic analysis was conducted using the constant comparison method. Data saturation was reached after 16 interviews. Results Most interviewees were still engaged in regular, predominantly informal, mindfulness practice, although some discontinued mindfulness practice and reported an ‘unchanged lifestyle’. Three main themes came forward; (1) ‘focused attention and open awareness’ during daily activities as core elements of long-term mindfulness practice; (2) ‘changes in behavior and coping’ that resulted from taking a pause, reflecting, recognizing automatic behavioral patterns and making space for a conscious response; (3) ‘integration in personal and professional life’ by enhanced enjoyment of daily activities, improved work-life-balance and making different career choices. Barriers and facilitators in starting and maintaining mindfulness practice were 1) understanding and intention as ‘pre-conditions’; (2) practical, personal and professional factors of students in maintaining practice. Conclusions Two years after participation in a MBSR training, many interviewees were still engaged in (mostly informal) mindfulness practice contributing to both personal and professional changes. In light of the high clerkship demands, MBSR training could be a valuable addition to medical curricula, supporting medical students in developing necessary competencies to become well-balanced professionals.